Sudden unexpected death from natural diseases: Fifteen years' experience with 484 cases in Seychelles. (January 2016) - Zhao, Peng; Wang, Ji-Gang; Gao, Peng; Li, Xia; Brewer, Rubell
Abstract: The aim of this study is to identify and subclassify sudden natural death (sudden death from natural diseases) cases in Seychelles. A total of 484 sudden natural death cases with autopsy at the Clinical Pathology Laboratory, Victoria Hospital, Seychelles between 1997 through 2012 were retrospectively reviewed. Among them, 363 cases (75%) were male and 121 (25%) were female. The most frequent sudden deaths were attributed to cardiovascular diseases (78.5%), and then followed by infectious diseases (9.9%), and gastrointestinal diseases (9.1%). This is the largest population-based study on sudden natural deaths in Seychelles. Highlights: This is the largest population-based study on sudden natural deaths in Seychelles. The sudden natural death happened more frequently in 40 and 50 years old males in Seychelles. The coronary artery diseases/myocardial infarction were the most common cause of sudden natural deaths in Seychelles.